Nearpod sebagai Media Interaktif dalam Pembelajaran Teks Resensi di Kelas VIII SMP Islam Nurul Fikri Serang - D, Fitria Anggraini; Marlinda, Silviani; Hilaliyah, Tatu (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to describe the use of Nearpod as an interactive media in learning review texts in grade VIII of SMP Islam Nurul Fikri Boarding School Serang. The method used is qualitative descriptive research with a case study approach. Data was collected through observation, interviews, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results show that Nearpod is able to increase the effectiveness of review text learning through interactive features that support active student engagement, such as quizzes, discussions, and multimedia presentations. The use of Nearpod makes it easier for teachers to deliver material dynamically and provide direct feedback to students. In addition, students became more motivated and enthusiastic in participating in learning, which was reflected in their increased participation and understanding of the structure and content of the review text.The conclusion of this study is that Nearpod is an effective learning medium to improve the quality of review text learning. This media not only helps students understand the material more deeply, but also creates an interesting and interactive learning atmosphere. This study recommends the application of Nearpod in other learning to support innovation in the technology-based learning process.